Additive Manufacturing Titanium Dental Implants Placed in Sinuses Grafted with 70HA:30-TCP: A One-Year Retrospective Study for Evaluation of Survival Rate - Mafra, Ilton José (2024)
The present short-term retrospective study evaluated the implant survival rate and peri-implant bone loss around additive-manufactured titanium implants placed in sinuses grafted with Plenum Osshp (Plenum Bioengenharia, Jundia, SP, Brazil) (70HA:30β-TCP) material. A total of 39 implants were inserted after 23 sinus floor elevation procedures in 16 consecutive patients. Prosthetic rehabilitation included fixed partial prostheses (three units), single crowns (eleven units), and fixed full arches (three units). Clinical and radiographic parameters of implant-supported restorations were evaluated after at least one year of occlusal loading. The implant–crown success criteria included the absence of pain, suppuration, and clinical mobility, an average distance between the implant shoulder and the first visible bone contact (DIB) < 1.0 mm from the initial surgery, and the absence of prosthetic complications at the implant–abutment interface. The overall cumulative implant survival rate was 97.43%. No prosthetic complications at the implant–abutment interface were reported. After one year, the mean DIB was 0.23 mm ± 0.14. Within the limits of this retrospective study, it can be concluded that 70 HA:30 β-TCP allowed stable and reliable bone support to maintain healthy conditions around titanium dental implants produced by additive manufacturing.